IbM KERAJINAN TENUN KELURAHAN NTOBO KOTA BIMA NUSA TENGGARA BARAT - Nurul Huda; Sri Ernawati; Mistar Mistar (Jurnal Akrab Juara, 2018)
Ntobo Sub-Village is one of the traditional sub-village that still maintains in the traditions and cultural values of Bima. The founding and Empowerment Program in Ntobo Sub-village was disturbed by the problems experienced by the weaving group, These are (1) The formation group of weaving craftsmen has not yet been established. And most weaving group members women and elderly whom to care and gave a priority to their children and husbands first, including cooking and preparing their clothes after these finished they can take care of the tasks that assigned by the group, (2) the development of shapes, colors or patterns and product model. The weaving craftsmen in Ntobo sub-Village acknowledged that one of the basic problems experienced by the weaving group is related to the products women shape color and products models and the geographical location of the Ntobo sub-district is in fact not from the city center of Bima , but until now must of the weaving groups in Ntobo sub-Village do not have a product marketing site, due to the lack of funds by the group. The approach used in solving the problems faced by the weaving group in Ntobo Sub-Village is through sosialisation approach, consultation and counseling, evaluation, with training methods and assistance in designing motifs and weaving patterns. Keywords: Weaving Group, Ntobo Sub-Village, Group Establishment and Motive Design